Peningkatan Kapasitas Kader sebagai Upaya Pencegahan dan Penanggulangan Hipertensi di Desa Mandiangin Timur - Nur Laily; Aliefia Meutia Luna; Fitriyani Fitriyani; Noor Hana Maulida; Nur Aisya Dinda Ayutami (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
Hypertension is a non-communicable disease with a high prevalence and is a major risk factor for serious complications such as stroke and heart disease. Low public awareness and limited capacity of health workers to provide education and early detection pose challenges in hypertension prevention efforts at the community level. The program “Capacity Building for Health Workers as an Effort to Prevent and Control Hypertension in Mandiangin Timur Village” was implemented by Field Learning Experience (PBL) Group 20 students in August 2025 in Mandiangin Timur Village, Karang Intan District, Banjar Regency. The intervention was carried out through interactive lectures, discussions, and the use of educational media in the form of posters, leaflets, and videos. The targets of the activity consisted of 17 cadres and 30 villagers. Knowledge evaluation using pre-tests and post-tests showed an increase in the average score of cadres from 95.28 to 96.46, while the community increased from 76 to 92.33. Blood pressure checks also showed that most participants were in stage 1–2 hypertension, emphasizing the need for ongoing education. This program proved effective in increasing the capacity of cadres and community knowledge about risk factors, prevention, and management of hypertension. In addition, this activity strengthened the role of cadres as agents of change in ongoing efforts to control hypertension at the village level.